The anatomy of dependence - Doi, Takeo (Kodansha International, 1973)
The Anatomy of Dependence by Takeo Doi is a look at one facet of Japanese society. Doi focuses on the aspect of unconditional love between parent and child and how it relates to the overarching characteristics of Japanese social structure. Doi relates many theories from many fields of study, notably psychology, anthropology, and sociology.